Inner Conflict of Dewa's Character in the Novel Invalidite by Faradita: A Study of Humanistic Psychology - Raja Gukguk, M Evelina; Dicky Rachmat Pauji; Kurnia Rachmawati (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
The objective of this research is to elucidate three key aspects related to Dewa's character in the novel "Invalidite": (1) the internal conflicts experienced by Dewa, (2) the various manifestations of these inner conflicts, and (3) an exploration of Dewa's unmet needs within the context of the novel "Invalidite." This research methodology uses a descriptive qualitative approach. Data collection techniques involve meticulous reading and note-taking, tailored to the primary data source, namely Faradita's novel "Invalidite." The researcher engaged in a thorough examination of the novel's text, systematically documenting all information about Dewa's inner conflicts. Additionally, relevant data such as words, sentences, or paragraphs depicting Dewa's inner conflicts, behaviors, and unfulfilled needs were identified and recorded. This research reveals distinct forms of inner conflict within Dewa's character, encompassing anxiety, trauma, fear, anger, and indecision. Furthermore, this research sheds light on Dewa's unmet needs as the primary drivers of his internal conflicts, specifically: (1) unfulfilled physiological need, (2) unmet need for security, (3) unmet need for love and affection, and (4) unmet need for recognition. In summary, this research provides a comprehensive understanding of the inner conflicts and unmet needs of Dewa's character in the novel "Invalidite," drawing on Abraham Maslow's framework. The identified forms of inner conflict and unfulfilled needs contribute to a nuanced exploration of Dewa's psychological landscape in the narrative.